Pengaruh Ketersediaan Modal Kerja dan Biaya Produksi Terhadap Pendapatan UMKM di Kecamatan Medan Timur Kota Medan - Al Firah; Feby Mumtaza (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2023)
This research is motivated by the declining UMKMs income in Medan. The decline in revenue is thought to be due to the lack of working capital availability with relatively high production costs. This study aims to determine the effect of the availability of working capital and production costs simultaneously on the UMKMs income in Medan. The population of the sample is 56 UMKMs in East Medan District. Collecting data using multiple linear regression. The results showed that partially the working capital availability variable showed a significant positive effect on UMKMs income in Medan, every increase in the working capital availability variable by 100% led to an increase in UMKMs income by 55.2%, meaning that the condition of working capital availability was not ideal (balanced). to support UMKM production activities. Partially it is known that the production cost variable shows a significant negative effect on the UMKMs income in Medan, every increase in the production cost variable of 100% causes a decrease in UMKMs income by 35.8%, meaning that production costs need to be evaluated so that the prices of goods produced are not too expensive. Simultaneously it is known that the variable availability of working capital and production costs shows a significant positive and negative effect on the UMKMs income in Medan. Based on the test results of the coefficient of determination (Adjust R Square) it is known that the variable availability of working capital and production costs can explain UMKMs income of 84.8%. While the rest (15.2.6%) can be explained by other factors not examined in this study.